The relationship between static and dynamic balances and lower extremity injuries in the adolescent athlete - Hassan Farhadi (Vesnu Publications, 2013)
Introduction: Sport is the leading cause of injuries requiring medical attention among adolescents. The purpose of this study was to investigate the relationship between static and dynamic balances and incidence of lower extremity injuries in adolescent athletes using functional tests. Materials and Methods: One hundred high-school male athletes participated in this study (mean age ± SD; 17.30 ± 1.44, weight ± SD; 69.92 ± 2.14, and height ± SD; 175.06 ± 7.43). They played soccer, volleyball, basketball and handball and had a history of lower extremity injury in past two years. A researcher used a form to record athletes' injuries information. To evaluate static and dynamic balances, the stork stand and star excursion balance tests were applied, respectively. Pearson's correlation coefficient and Fisher's Z test were used for statistical analysis at the significant level of 0.05. All data were analyzed by SPSS, version 17. Results: Findings indicated that there is a negative significant correlation between static and dynamic balance and incident of lower extremity injuries in adolescent athletes (r = -0.620, P < 0.05). Conclusion: Core stabilizer muscles and neuromuscular control deficit might cause a poor balance and predispose adolescent athlete exposure to injury. So, the role of balance in training programs should be highlighted to reduce the injury potential and could be considered as an integral part in their training sessions. Keywords: Adolescent athletes, Static balance, Dynamic balance, Lower extremity injury